Clarity of objectives and working principles enhances the success of biomimetic programs. (22nd September 2017) - Wolff, Jonas O; Wells, David; Reid, Chris R; Blamires, Sean J
Abstract: Biomimetics, the transfer of functional principles from living systems into product designs, is increasingly being utilized by engineers. Nevertheless, recurring problems must be overcome if it is to avoid becoming a short-lived fad. Here we assess the efficiency and suitability of methods typically employed by examining three flagship examples of biomimetic design approaches from different disciplines: (1) the creation of gecko-inspired adhesives; (2) the synthesis of spider silk, and (3) the derivation of computer algorithms from natural self-organizing systems. We find that identification of the elemental working principles is the most crucial step in the biomimetic design process. It bears the highest risk of failure (e.g. losing the target function) due to false assumptions about the working principle. Common problems that hamper successful implementation are: (i) a discrepancy between biological functions and the desired properties of the product, (ii) uncertainty about objectives and applications, (iii) inherent limits in methodologies, and (iv) false assumptions about the biology of the models. Projects that aim for multi-functional products are particularly challenging to accomplish. We suggest a simplification, modularisation and specification of objectives, and a critical assessment of the suitability of the model. Comparative analyses, experimental manipulation, and numerical simulations followed by tests of artificial models have led to the successful extraction of working principles. A searchable database of biological systems would optimize the choice of a model system in top-down approaches that start at an engineering problem. Only when biomimetic projects become more predictable will there be wider acceptance of biomimetics as an innovative problem-solving tool among engineers and industry.